Microsoft PowerPoint 2000 : quick tutorial - Murphy, Patricia. (South-Western Educational, 2000)
This book is about: Getting started with PowerPoint; Creating a Presentation; Text Editing and Formatting; Working with graphic objects; Inserting tables and charts; Additional PowerPoint features; and Delivering the presentation.